Making lighting adjustments to establish new behavioral patterns in a child with autism: A follow-up study - Piven, Emily; Derakhshanrad, Seyed Alireza (Iranian Journal of Child Neurology, 2022)
The behavioral patterns of children with autism are thought to be comprised of interconnected parameters. Acknowledging the value of lighting parameter, a less-studied aspect of the physical environment, this study illustrates how such parameter could contribute to increasing attention to visual stimuli. This paper outlines the establishment of new behavioral patterns following a novel approach using blacklight conditions, which highlighted objects in the foreground of the blackened environment, to modify the visual environment surrounding a child with autism. The child was first attracted to objects in the environment under blacklight conditions. This paper offers healthcare practitioners a useful perspective that has the potential to address a very important aspect of how a child with autism developed interaction with the objects following an environmental modification.